First we arrange, so that it is:
x^2 +4x - 3 =0
which is now in the form ax^2+bx+c=0
If you have this question, I'm assuming you should know the equation to solve for x:
x= (-b+√(b^2-4ac))/2a or x=(-b-√(b^2-4ac))/2a
In our case, a=1, b=4, c=-3 SO:
x=(-4+√(16+12))/2=(-4+√28)/2= -2+√7
or
x=(-4-√(16+12))/2=(-4-√28)/2= -2-√7
2007-02-26 04:39:15
·
answer #1
·
answered by Kerynella 2
·
0⤊
0⤋
after you rewrite it as x² + 4x - 3 = 0, you might try completing the square:
x² + 4x ..... = 3
x² + 4x + 4 = 3 + 4
(the added 4 is the 4 in front of x, divided by 2, and then squared)
(x + 2)² = 7
x + 2 = ±√7
x = -2 ±√7
2007-02-26 04:46:50
·
answer #2
·
answered by Philo 7
·
1⤊
0⤋
x^2+4x+4=7
Step1 set the equation to zero
how
Subtract both side by (-7)
x^2+4x+4-7=0
x^2+4x-3=0
use the quadratic formula (check any math books)
X1=(-b+((b^2)-4ac)^1/2)/(2a)
X2=(-b-(b^2)-4ac)^1/2)/(2a)
Raised to the half power means square root
a=1 , b=4 ,c =-3
plug the number in the quadratic formula
Shoul be
X1=-2+(7)^1/2
x2=-2-(7)^1/2
2007-02-26 05:04:13
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
x^2+4x -3=0
here a =1 b=4, c=-3
b^2-4ac = 16- 4(1)*(-3) =28
sqrt(b^2-4ac) =sqrt (28)
so
x= {-b +/- sqrt (b^2-4ac)}/2a
x= {-4 +sqrt (28)}/2 and {-4 -sqrt(28)}/2
2007-02-26 04:45:29
·
answer #4
·
answered by UnENG 3
·
0⤊
0⤋
x = -14/3
2007-02-26 04:43:08
·
answer #5
·
answered by The Dude 2
·
0⤊
0⤋